Differences in local versus systemic TNFα production in COPD: inhibitory effect of hyaluronan on LPS induced blood cell TNFα release. Issue 6 (3rd March 2006) - Dentener, M A; Louis, R; Cloots, R H E; Henket, M; Wouters, E F M
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is characterised by both airway inflammation and systemic changes. To elucidate the relationship between local and systemic inflammation, tumour necrosis factor α (TNFα) production by sputum cells and blood cells of patients with COPD and controls was compared and the effect of the extracellular matrix compound hyaluronan (HA) on TNFα release was studied. Methods: Four study groups were included: 10 steroid free COPD patients, 8 steroid treated patients, 10 healthy smokers, and 11 healthy non-smokers. Sputum cells and blood were incubated for 24 hours with or without lipopolysaccharide (LPS) in the absence or presence of HA (122 kDa or HMW fragment). TNFα was measured by ELISA. Results: Sputum cells produced spontaneously high levels of TNFα but were unresponsive to LPS. Sputum cells from COPD patients (both steroid free and steroid treated) produced significantly less TNFα than cells from healthy non-smoking subjects (p = 0.017 and p = 0.001, respectively). In contrast, blood cells produced TNFα only in response to LPS. No differences were observed in TNFα production by blood cells between the patient groups and the control groups. HA (both fragments) partially blocked LPS (1 ng/ml) induced TNFα release by blood cells from all study groups, whereas TNFα production by sputum cells was not influenced by HA. Conclusion: These data indicate a difference between local and systemic TNFα production. Sputum cells of patients with COPD produced less TNFα than controls, which could contribute to impaired local defence. An inhibitory effect of HA on TNFα release in blood cells was observed which was similar in both patients and controls.